Real‐world EGFR testing in patients with stage IIIB/IV non‐small‐cell lung cancer in North China: A multicenter, non‐interventional study. Issue 11 (25th September 2018) - Cheng, Ying; Wang, Yan; Zhao, Jun; Liu, Yunpeng; Gao, Hongjun; Ma, Kewei; Zhang, Shucai; Xin, Hua; Liu, Jiwei; Han, Chengbo; Zhu, Zhitu; Wang, Yan; et al.
Abstract : Background: Before tyrosine kinase inhibitor (TKI) therapy can be administered in patients with advanced non‐small cell lung cancer (NSCLC), EGFR mutation testing is required. However, few studies have evaluated the extent of EGFR testing in real‐world practice in China. Methods: A multicenter, observational study of EGFR testing in NSCLC patients in North China was conducted. Treatment‐naïve patients or those with postoperative recurrent stage IIIB/IV NSCLC were enrolled. The primary objective was EGFR testing rate. Secondary objectives included EGFR mutation status, EGFR testing methods and specimens, factors associated with EGFR testing, and overall survival with or without EGFR testing. Results: Overall, 2809 patients with stage IIIB/IV NSCLC were enrolled; 90.78% had adenocarcinoma. The EGFR screening rate was 42.54%. EGFR testing rates were higher in tumor samples obtained by lymph node puncture, and in patients with urban medical insurance, adenocarcinoma, non‐smokers, or those located in developed cities (all P < 0.001). The EGFR mutation rate was 46.44%. The most commonly used specimens for EGFR testing were biopsy tumor samples (67.53%). PCR‐based methods (72.05%), Sanger sequencing (5.36%), and Luminex liquid chip (5.10%) were the most frequently used testing platforms. Similar positive EGFR mutation rates were achieved with different platforms. TKI therapy was the first‐line treatment administered to most EGFR ‐positive patients (56.22%), and chemotherapy in EGFR ‐negative patients (84.88%). Overall survival was higher in EGFR‐tested than in untested patients (27.50 vs. 19.73 months; P = 0.007). Conclusion: Real‐world EGFR testing rates for NSCLC in North China were relatively low because of clinical and social factors, including medical insurance coverage.